2009
DOI: 10.1002/bip.21271
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal truncated pyroglutamyl β amyloid peptide Aβpy3‐42 shows a faster aggregation kinetics than the full‐length Aβ1‐42

Abstract: We tested directly the differences in the aggregation kinetics of three important beta amyloid peptides, the full-length Abeta1-42, and the two N-terminal truncated and pyroglutamil modified Abetapy3-42 and Abetapy11-42 found in different relative concentrations in the brains in normal aging and in Alzheimer disease. By following the circular dichroism signal and the ThT fluorescence of the solution in phosphate buffer, we found substantially faster aggregation kinetics for Abetapy3-42. This behavior is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 44 publications
6
59
0
Order By: Relevance
“…Recently, it was demonstrated that, in similar initial buffer conditions and using three different techniques (flow cytometry, ThT fluorescence and circular dichroism), these N-terminal modified peptides aggregate much faster than the fulllength Aβ (D'Arrigo et al, 2009;Shilling et al, 2006). Altogether, the aggregation kinetics of Apy3-42 was found 20-250 by cytometry and ThT fluorescence (Shilling et al, 2006) and more than 30 times by CD (D'Arrigo et al, 2009) faster than that of A1-42 respectively, depending upon the assay method.…”
Section: Comparison Of N-truncated and Pyromodified A To Full-lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it was demonstrated that, in similar initial buffer conditions and using three different techniques (flow cytometry, ThT fluorescence and circular dichroism), these N-terminal modified peptides aggregate much faster than the fulllength Aβ (D'Arrigo et al, 2009;Shilling et al, 2006). Altogether, the aggregation kinetics of Apy3-42 was found 20-250 by cytometry and ThT fluorescence (Shilling et al, 2006) and more than 30 times by CD (D'Arrigo et al, 2009) faster than that of A1-42 respectively, depending upon the assay method.…”
Section: Comparison Of N-truncated and Pyromodified A To Full-lengthmentioning
confidence: 99%
“…Altogether, the aggregation kinetics of Apy3-42 was found 20-250 by cytometry and ThT fluorescence (Shilling et al, 2006) and more than 30 times by CD (D'Arrigo et al, 2009) faster than that of A1-42 respectively, depending upon the assay method. The oligomers that form β-structure rapidly are found to be more toxic (D'Arrigo et al, 2009;Mastrangelo et al, 2006;Shilling et al, 2006). In addition the aggregation pathway of the two A leads to more toxic dynamic oligomeric states for Apy3-42 and to fibril formation for A1-42, see for instance (D'Arrigo et al, 2009) and (He & Barrow, 1999), while when the two are mixed (e.g.…”
Section: Comparison Of N-truncated and Pyromodified A To Full-lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…To complicate the understanding further, research has shown N-terminally modified Aβ peptides, with the most prominent forms identified starting at amino acid 3 or 11 and possessing Nterminal pyroglutamic acid (pyroE), generated from glutamic acid by the enzyme glutaminyl cyclase [109], [110]. In vitro studies have shown that small N-terminal deletions accelerate Aβ aggregation into neurotoxic fibrils compared to Aβ 1-42 [111], [112]. In the case of pyroglutamylation, the increased propensity to aggregate might be due to the higher hydrophobicity of the peptide when losing one or two charges [113] and limited N-terminal degradation [109].…”
Section: Aβ Length Dependent Toxicitymentioning
confidence: 99%